Online form of Sustainable Land Management (SLM) option by context (English version). - Fradi, Fajr; Diwediga, Badabate; Hamdan, Mahdi; Al-Najdawi, Moayad; Le, Quang Bao; Bonaiuti, Enrico; Jaspe, Jim; Ayyash, Bashar (2017)
This is the presentation of Fajr Fradi during the workshop "Sustainable Land Management to Achieving Land Degradation Neutrality: Options-by-Context Approach and Tool", final workshop for the project "Impact Evaluation of SLM Options to Achieve Land Degradation Neutrality", held in Tunis on the 24th October 2017. This presentation highlights the new interfaces of the SLM component of the GeOC tool.